SUBJEK DAN OBJEK EVALUASI PENDIDIKAN DI SEKOLAH/MADRASAH TERHADAP PERKEMBANGAN REVOLUSI INDUSTRI 5.0 - Fatma Wati; Siti Kabariah; Adiyono Adiyono (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Evaluation is a tool used to measure the success of a project. To measure something must use the correct measuring instrument based on existing indicators. Educational assessment is related to educational activities or processes that are the center of attention. The object of assessment is cognitive (knowledge and understanding), affective (attitudes and ideals), and psychomotor (skills and habits), adjusting the identified instruments to the aspects to be assessed. and the subject of assessment is the teacher or lecturer who teaches certain subjects. The subjects and objects of learning evaluation in schools/madrasas can include various aspects related to the process and learning outcomes of students in the school. The subject and object of evaluating education in schools/madrasas against the development of the Industrial Revolution 5.0 involves aspects relevant to technological transformation and changes in the world of work.